Fractography of Modern Engineering Materials: Composites and Metals, Second Volume 1993
DOI: 10.1520/stp14900s
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Fracture Surface Analysis of Fatigue Crack Propagation Under Variable Amplitude Loading

Abstract: A method for quantitative analysis of fatigue fracture surfaces has been developed in our laboratory. Firstly, the salient features of the proposed method are presented based on the results obtained under constant amplitude (CA) tests at five R ratios for the 2024 T351 aluminum alloy. Secondly, the proposed method is applied to fatigue crack growth under variable amplitude loading. Two kinds of tests were studied, simple block loading (BL) consisting of four mean load levels with different numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A method for quantitative analysis of fatigue fracture surfaces is proposed, the following technique method presented in 14,15 is used.…”
Section: Methodsmentioning
confidence: 99%
“…A method for quantitative analysis of fatigue fracture surfaces is proposed, the following technique method presented in 14,15 is used.…”
Section: Methodsmentioning
confidence: 99%
“…The change in behaviour from low to high growth rates was associated with a change in To determine the ECA loading a critical analysis of the global fracture surface appearance was carried out [15]. It was shown that the global fracture surface evolution characterized by the percentage area covered by striations, pseudo cleavage facets, and dimples depends upon the K, , value and the R ratio for CA conditions.…”
Section: Energy Based Eca Determinationmentioning
confidence: 99%
“…Ranganathan and coworkers [18] identified facets, striations, and dimples as salient features on fracture surfaces of three aluminum alloys and developed a grid technique to quantify their spatial distributions. Plots of percent area of the feature versus load parameters showed that peak to peak load ratio and maximum stress intensity factor are most important in determining fracture surface appearance.…”
Section: Introductionmentioning
confidence: 99%